Recent developments in the treatment of obstructive sleep apnea - Verse, Thomas; Pirsig, Wolfgang; Stuck, Boris; Hörmann, Karl; Maurer, Joachim T. (American journal of respiratory medicine, 2003)
Modern sleep medicine has been in existence for only 20 years and therefore has to be regarded as a comparatively recent field of specialization. For this reason it is not surprising that there are numerous new trends and developments concerning the treatment of sleep-related breathing disorders. This review focuses on developments in the treatment of obstructive sleep apnea (OSA) over the last 5 years.